2010
DOI: 10.1002/cncr.25730
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a clinic‐based colorectal cancer screening promotion program for underserved Hispanics

Abstract: BACKGROUND: Hispanics in the United States are less likely than other groups to receive screening services for colorectal cancer. METHODS: The authors conducted a clinic-based individual randomized trial that enrolled Hispanic patients ages 50 to 79 years who had been seen in the Seattle-based community clinic in the past 5 years. A total of 501 patients met the eligibility criteria and were randomized to 1 of 3 conditions: 1) usual care; 2) mailed fecal occult blood test (FOBT) card and instructions on how to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
115
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(122 citation statements)
references
References 21 publications
5
115
2
Order By: Relevance
“…Those that have evaluated this intervention in more vulnerable populations have tended to focus on just 1 or 2 ethnic groups. 12,20 Our study adds to this existing literature by demonstrating that this outreach strategy can significantly improve colorectal cancer screening rates even among economically disadvantaged patients from a wide range of racial, ethnic, and cultural backgrounds.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Those that have evaluated this intervention in more vulnerable populations have tended to focus on just 1 or 2 ethnic groups. 12,20 Our study adds to this existing literature by demonstrating that this outreach strategy can significantly improve colorectal cancer screening rates even among economically disadvantaged patients from a wide range of racial, ethnic, and cultural backgrounds.…”
Section: Discussionmentioning
confidence: 69%
“…Those that have evaluated this intervention in more vulnerable populations have tended to focus on just 1 or 2 ethnic groups. 12,20 Our study adds to this existing literature by demonstrating that this outreach strategy can significantly improve colorectal cancer screening rates even among economically disadvantaged patients from a wide range of racial, ethnic, and cultural backgrounds.Especially in settings with an EHR system to facilitate the ready identifi cation of patients who are eligible and overdue for colorectal cancer screening, the direct mailing of FOBT kits to eligible patients with some additional phone outreach to initial nonresponders may be a sustainable strategy to promote colorectal cancer screening, particularly under a patient-centered medical home payment model that reimburses practices for population health management activities.21 Although our study did not include formal cost or cost-effectiveness analyses, very similar outreach interventions have been found to be cost-effective in other studies. 15,16 Our study demonstrated that the direct-to-patient outreach intervention was effi cacious even in a health care setting that had already implemented point-ofcare clinician-directed electronic clinical reminders to promote appropriate colorectal cancer screening.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…13 Several randomized trials have reported that outreach with FOBT can improve CRC screening rates. [14][15][16][17][18][19][20] However, most were conducted in integrated health plans. 15 , 16 , 18 , 19 Few targeted vulnerable populations cared for in community health centers (CHCs) and other safety net settings.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] However, most were conducted in integrated health plans. 15 , 16 , 18 , 19 Few targeted vulnerable populations cared for in community health centers (CHCs) and other safety net settings. [21][22][23][24] We previously reported that a multifaceted outreach and reminder intervention using mailed FITs increased adherence to annual screening, compared to point-of-care strategies that maximize FIT distribution at clinic visits, for patients due for repeat screening.…”
Section: Introductionmentioning
confidence: 99%